Enhanced risk of multiple sentinel lymph node basins in truncal and head and neck melanoma - Harmeet K Bhullar; Lipi Shukla; Ramin Shayan; Frank Bruschino-Raiola (Australasian Journal of Plastic Surgery)
# Introduction